THE RELATIONSHIP A BETWEEN LEADERSHIP STYLE AND WORKING CONDITIONS WITH NURSES 'WORKING SATISFACTION IN INPATIENT ROOMS, BAHTERAMAS HOSPITAL: NURSES' WORKING SATISFACTION - Nur Ardiana; La Ode Saafi; Tasnim Tasnim (STIKes Mandala Waluya Kendari, 2021)
Background:From the preliminary study by the researcher with the inpatient nursing department through in-depth interviews, there were problems such as complaints from patients who were in pain, there were nurses who did not come immediately and provide nursing care. Through interviews with nurses, it was found that career development procedures had not been prepared in nursing management. In addition, there are nurses who are several times late more than the stipulated time. Then there are still complaints that the incentives received are still insufficient. Methods:This type of research uses quantitative research with a cross sectional design. The population was 257 all nurses in the inpatient room at Bahteramas Hospital, with a sample of 141 samples using simple random sampling. Results:Using the cramer coefficient, it is obtained a value of 0.732, this shows the strength of the relationship between leadership style in work and job satisfaction of nurses. And the cramer coefficient is obtained a value of 0.620, this shows the strength of the relationship between leadership style in work and job satisfaction of nurses in the inpatient room at Bahteramas Hospital in the strong relationship category. Conclusion:There is a relationship between leadership style and working conditions on the job satisfaction of nurses in the inpatient room of the Bahteramas Hospital.